2019
DOI: 10.3389/fmicb.2019.01759
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Demethylase-Independent Role for the H3K4-Specific Histone Demethylases in Aspergillus nidulans and Fusarium graminearum Secondary Metabolism

Abstract: Fungi produce a plethora of secondary metabolites (SMs) involved in cellular protection, defense, and signaling. Like other metabolic processes, transcription of SM biosynthesis genes is tightly regulated to prevent an unnecessary use of resources. Genes involved in SM biosynthesis are usually physically linked, arranged in secondary metabolite gene clusters (SMGCs). Research over the last decades has shown that chromatin structure and posttranslational modifications (PTMs) of histones represent important laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 79 publications
2
21
0
Order By: Relevance
“…Recently, some studies have showed that histone demethylases, such as KdmA, an H3K9/36me3 demethylase, play a role in transcriptional regulation in A. nidulans (Agger et a l ., 2007 & 2019; Matthews et al, 2015). This finding suggests that these UTX-like containing COMPASS-like complexes and their associated bivalent H3K9/27 demethylase and H3K4me3 methyltransferase activities may be involved in dynamic target gene activation (Bernstein et al, 2006; Amar et al, 2015;Bachleitner et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies have showed that histone demethylases, such as KdmA, an H3K9/36me3 demethylase, play a role in transcriptional regulation in A. nidulans (Agger et a l ., 2007 & 2019; Matthews et al, 2015). This finding suggests that these UTX-like containing COMPASS-like complexes and their associated bivalent H3K9/27 demethylase and H3K4me3 methyltransferase activities may be involved in dynamic target gene activation (Bernstein et al, 2006; Amar et al, 2015;Bachleitner et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(Connolly et al, 2013; Palmer et al, 2013; Matthews et al, 2016). In F. graminearum , FgSet1 is a Set1 orthologue and is one subunit of the COMPASS-like complex, which also plays an important role in regulating fungal growth and secondary metabolism (Connolly et al, 2013; Liu et al, 2015; Bachleitner et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the individual genes within a given BGC are transcriptionally co-regulated, not expressed by default and activated only in response to a “proprietary” expression signal. For most of these clusters, standard laboratory conditions do not generate this critical signal and consequently, their cognate products cannot be identified (Bachleitner et al 2019 ; Chujo and Scott 2014 ; Connolly et al 2013 ; Gacek-Matthews et al 2016 ; Gacek and Strauss 2012 ; Reyes-Dominguez et al 2010 ; Studt et al 2016 ). About 50% of the BGCs contain a gene that encodes a pathway-specific transcriptional activator (Keller 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For most of these clusters, standard laboratory conditions do not generate this critical signal and consequently they are silent. (Bachleitner et al, 2019;Chujo and Scott, 2014;Connolly et al, 2013;Gacek-Matthews et al, 2016;Gacek and Strauss, 2012;Reyes-Dominguez et al, 2010;Studt et al, 2016). In about 50% of the cases the SM BGCs contain a gene that encodes for a transcriptional activator (Keller, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Because of these complications and limitations of established techniques there are still hundreds of predicted fungal BGCs awaiting the characterisation of their cognate metabolite (Lyu et al, 2020). Other approaches that interfere with chromatinbased regulators, such as histone deacetylases (Shwab et al, 2007;Studt et al, 2013), histone methyl transferases (Chujo and Scott, 2014;Connolly et al, 2013;Studt et al, 2016),histone demethylases (Bachleitner et al, 2019;Gacek-Matthews et al, 2016), etc. may work for some clusters, but not for others.…”
Section: Introductionmentioning
confidence: 99%